2017
DOI: 10.1002/pc.24416
|View full text |Cite
|
Sign up to set email alerts
|

Improved mechanical and wear resistance properties of silicon carbide/poly (vinyl alcohol) composites by silane coupling agents

Abstract: In this work, the surface coated silicon carbide (SiC) obtained by dispersing it in silane coupling agent/ethanol solutions of different concentrations was used as a filler in poly (vinyl alcohol)(PVA) and the composites of (PVA)/SiC were prepared by melt process. The structure and properties of PVA/SiC composites were studied by Fourier‐transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), mechanical and wear resistance tests in detail. The silane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Silicon carbide (SiC) is an analogue of graphene and a binary compound of carbon and silicon, which is the most widely used and economical one in the contemporary nonoxide refractory materials . Fabrication the composites with SiC has been drawing a special attention as an alternative supported material for the high thermal stability and good mechanical properties . Previous research showed that polyurethane elastomer composites exhibited better mechanical property, solvent resistance, and wear resistance by silicon carbide incorporation .…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is an analogue of graphene and a binary compound of carbon and silicon, which is the most widely used and economical one in the contemporary nonoxide refractory materials . Fabrication the composites with SiC has been drawing a special attention as an alternative supported material for the high thermal stability and good mechanical properties . Previous research showed that polyurethane elastomer composites exhibited better mechanical property, solvent resistance, and wear resistance by silicon carbide incorporation .…”
Section: Introductionmentioning
confidence: 99%
“…A silane coupling agent is a desirable additive for enhancing the performance of composites by improving the interfacial compatibility of the two phases . In our previous studies, we proved that the surface modification of inorganic fillers by silane highly improved the interfacial adhesion between the filler and matrix; this led to enhanced mechanical properties …”
Section: Introductionmentioning
confidence: 85%
“…42,43 In our previous studies, we proved that the surface modification of inorganic fillers by silane highly improved the interfacial adhesion between the filler and matrix; this led to enhanced mechanical properties. 44 In this study, PUI foams filled with different contents of EG were prepared from polyphenyl polymethylene isocyanate (PAPI), pyromellitic dianhydride (PMDA), and polyether polyol to improve the mechanical, thermal, and flame-resistant properties of PUI foams. Meanwhile, the surface modification of EG by a silane coupling agent was adopted with the aim of further improving the comprehensive performance of the PUI foams.…”
Section: Introductionmentioning
confidence: 99%
“…For nanofiller reinforced composite materials, the interaction, and compatibility between the filler and matrix would be a key parameter for the reinforcing effect. Especially, the mechanical properties of a nanocomposite greatly depend on the dispersion of nanoparticles in the polymeric matrix as well as interfacial bonding between filler and the polymeric matrix . The common methods to achieve good compatibility and dispersion include surface coating or surface chemical modification of the nanoparticles, incorporation of compatibilizers, etc .…”
Section: Introductionmentioning
confidence: 99%